Destination Branding And The Impact Of Perceived Quality And Image On The Loyalty - Bobovnický, Artur (Communication Today, 2025)
The importance of country brand image has been assessed and based on the reviews of recent developments in nation branding worldwide. To evaluate the loyalty of the visitors the impact of satisfaction and brand image has been evaluated.Quantitative data from Czech Republic have been utilized and PLS modelling was used to evaluate the relative impact of satisfaction and brand image.